Pengaruh Penambahan Butanol Sebagai Campuran Bahan Bakar Premium Terhadap Torsi dan Daya Mesin Bensin Dengan Sistem EGR - Firman Lukman Sanjaya; Syarifudin (Accurate: Journal of Mechanical Engineering and Science, 2020)
Increased vehicle volume causes a high use of fossil fuels and increased exhaust emissions. Butanol is a renewable fuel that can replace fossil fuels. This is because butanol has better characteristics than gasoline such as high octane value and oxygen content. This results in a more complete combustion process in the combustion chamber so that engine torque and power increase. This study was to observe the effect of using butanol on torque and power in gasoline engines with the EGR system. This test is carried out using a constant engine speed of 2500 rpm. The percentage of butanol in premium fuel is 5%, 10% and 15% of the total fuel volume. The test results show that the addition of 5% butanol to premium fuel can increase torque by 4.88% using a cold EGR system. Engine power experienced the highest increase in the addition of 15% butanol using a cold EGR system of 15.6 kW.